2020
DOI: 10.1371/journal.pone.0244578
|View full text |Cite
|
Sign up to set email alerts
|

Impaired large numerosity estimation and intact subitizing in developmental dyscalculia

Abstract: It is believed that the approximate estimation of large sets and the exact quantification of small sets (subitizing) are supported by two different systems, the Approximate Number System (ANS) and Object Tracking System (OTS), respectively. It is a current matter of debate whether they are both impaired in developmental dyscalculia (DD), a specific learning disability in symbolic number processing and calculation. Here we tackled this question by asking 32 DD children and 32 controls to perform a series of tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…Two broad hypotheses -numerosity deficit and symbolmagnitude mapping deficit -advocate a domain-specific disorder, whereas the executive function (EF) hypothesis posits domain general issues. The numerosity deficit hypothesis proposed a core deficit in processing quantity (Butterworth et al, 2011) and number sense (Dehaene et al, 2004;Decarli et al, 2020). The symbol-magnitude mapping deficit hypothesis proposed a specific weakness in automatically mapping symbols to their internal magnitude representations (Rubinsten and Henik, 2006;Rousselle and Noel, 2007).…”
Section: The Theoretical Perspective: Historymentioning
confidence: 99%
“…Two broad hypotheses -numerosity deficit and symbolmagnitude mapping deficit -advocate a domain-specific disorder, whereas the executive function (EF) hypothesis posits domain general issues. The numerosity deficit hypothesis proposed a core deficit in processing quantity (Butterworth et al, 2011) and number sense (Dehaene et al, 2004;Decarli et al, 2020). The symbol-magnitude mapping deficit hypothesis proposed a specific weakness in automatically mapping symbols to their internal magnitude representations (Rubinsten and Henik, 2006;Rousselle and Noel, 2007).…”
Section: The Theoretical Perspective: Historymentioning
confidence: 99%
“…In contrast, individual variability in subitizing capacity has not been reliably associated with arithmetic skills ( Anobile et al, 2019 ). Moreover, individuals with specific difficulties in mathematics (developmental dyscalculia) show impaired numerosity estimation ( Piazza et al, 2010 ; Mazzocco et al, 2011a ) but intact subitizing capacity ( Decarli et al, 2020 ; but see Schleifer and Landerl, 2011 ). Conversely, impaired subitizing (but not estimation) has been observed in individuals with Down syndrome ( Sella et al, 2013 ), who are also known to suffer from visuospatial working memory deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The association between subitizing and one’s mathematical abilities on surface seems to imply subitizing is numerical in nature. However, recent studies have also shown that subitizing ability does not necessarily predict one’s math abilities ( Anobile et al, 2019 ), as well as that developmental dyscalculia is not always associated with impairment in subitizing ability ( Decarli et al, 2020 ). As such, theorists have proposed other attentional or pattern recognition mechanisms that are not necessarily numerical in nature to account for findings in subitizing.…”
Section: Introductionmentioning
confidence: 99%